Wymiar społeczny zdrowia = The social dimension of health - Walentynowicz-Moryl, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main aim of this article is to overview the definitions of the social dimension of human health. This dimension occurs in the literature within the multi-dimensional health models. This approach assumes that the health of an individual is a complex phenomenon far exceeding the biological aspects of human activity. An individual is treated as a so-called ?whole person?. The authors mention from three to six health dimensions in the discussed publications. The social dimension can be found in each of them. Researchers agree that this is one of the fundamental dimensions.
Keywords: zdrowie; wielowymiarowe modele zdrowia; wymiar społeczny zdrowia; health; multidimensional health models; social dimension of health